Subgrouping University Students Based on Substance Use Pattern: A Latent Class Analysis - Karimirad, Mohammad Reza (Subst Abuse Rehabil, 2020)
PURPOSE: High-risk behaviors are the main causes of death and disability among youth and adults. Entering university might cause students to go through their first-hand experience of using substances. AIM: This study aimed to detect the subgroups of students based on substance use and assess the effects of religiosity and parental support as well as other related factors on the membership of students in each latent class. METHODS: Using a multistage sampling method, this cross-sectional study was conducted in 2016 in Hormozgan University of Medical Sciences (n=524). All students completed a self-report questionnaire. This questionnaire contained questions about substance use, religious beliefs and familial support. The questions of substance use were prepared using the World Health Organization Alcohol, Smoking and Substance Involvement Screening Test (WHO ASSIST). To analyze the data, PROC LCA statistical method was run in SAS9.2. RESULTS: Three latent classes were identified: 1) nonuser (87.5%), 2) tobacco and illicit drug user (8.7%) and 3) polydrug user (3.8%). Having extramarital sex in the last month (OR=28.29, 95% CI; 8.45–94.76), living alone (OR=4.29, 95% CI; 1.01–18.35) and having a higher score of familial support (OR=0.94, 95% CI; 0.89–0.98) were associated with the polydrug user class. Hookah smoking had the highest (11.1%) and non-medical methylphenidate use had the lowest (2.3%) prevalence among the participants of the study. CONCLUSION: This study revealed that 12.5% of the students were either tobacco and illicit drug users or polydrug users. Thus, focusing on the religiosity and familial support may help design some preventive programs for this stratum of young adults.